Alexandrella wimdecocki sp. nov. (Stilipedidae Holmes, 1908) and new records for three Australian Abyssal Amphipods (Crustacea: Peracarida) - Springthorpe, Roger T.; Hughes, Lauren E. (Zootaxa, 2025)
Four abyssal amphipod species from Four families are documented including the new species Alexandrella wimdecocki (Stilipedidae). The species, Amathillopsis australis Stebbing, 1883 from the family Amathillopsidae is reported for the first time since it was originally described from a single specimen and is now documented with six specimens. The Cyphocarids were recently reviewed (Hughes & Lowry, 2015) and additional records of Cyphocaris anonyx Boeck, 1871 are provided here, doubling the number of specimens known from the Australian fauna from four to eight. New records of the pardaliscid species Octomana hadromischa Hendrycks & Conlan, 2003 are a considerable range extension from the North Eastern Pacific to the new records in the Tasman Sea. These records of rare species are an exciting contribution to our knowledge of Australian abyssal amphipods.